Salix aegaea (Salicaceae), a new species from island of Ikaria (Greece) - Cambria, Salvatore; Brullo, Cristian; Giusso Del Galdo, Gianpietro; Sciandrello, Saverio; Siracusa, Giuseppe; Brullo, Salvatore (Phytotaxa, 2020)
A new species of willow from Ikaria Island (Greece), named Salix aegaea, is described and illustrated. For the leaf shape, as well as for the hairy ovary, capsule and base of stamina filaments, it shows close relationships with the species belonging to S. apennina group. It is morphologically well differentiated in several features regarding the shape and size of branches, leaves, inflorescences, floral bracts, ovaries, stamens and capsules, as well as the structure of leaf epicuticular waxes and hairs. Considerations on its ecology, chorology, leaf micro-morphology, conservation status and the identification keys including the allied species are also provided.